ANALISIS PENJUALAN ARANG SEKAM PADI MELALUI MEDIA SOSIAL FACEBOOK PADA USAHA MIKRO HAND - Bilhaq, Nataqa Yantiqu; Mashudi, Mashudi; Warneri, Warneri (Universitas Tanjungpura, 2024)
The purpose of this study is to ascertain the sales analysis of rice husk charcoal goods on Facebook for the Micro Hand company. The research techniques used are qualitative descriptive methodologies. The owner of the Micro Hand company and a devoted client are the sources of the research's information. The information was obtained through interviews. The study's findings demonstrate the value of using technology to increase the sale of rice husk charcoal through the use of Facebook social media.The business of Micro Hand was successfully conducted, and this was based on thorough research as well as the application of business methods or indicators, such as good pricing, the effectiveness of marketing media, and the sales effectiveness of products. Media marketing plan for selling rice husk charcoal goods Facebook social can be said to achieve marketing with clear objectives to achieve a business that meets sales targets with the implementation of a number of strategies, including indicators: increasing the variety of products offered by consumers; utilizing technology and social media in product marketing; offering prompt and courteous customer service; and conducting successful promotions. This implies more business for Micro Hand. These indicators already employ a marketing strategy for husk charcoal that is appropriate for the market and facilitates the faster development of the company.